Identifying Local Potentials in Lampung Province as a Biology Learning Resource - Fitri Nurfatonah; Tien Aminatun (Jurnal Penelitian Pendidikan IPA, 2025)
The integration of local potential into biology education is essential for enhancing student engagement, creativity, and environmental awareness. However, its implementation remains suboptimal in various regions, including Lampung Province. This study aims to identify and analyze the diversity of bird species in Way Kambas National Park (WKNP) as a potential biology learning resource. Using a descriptive exploratory approach with the point count method, observations were conducted at three locations within WKNP, identifying 33 bird species from 21 families, with a total of 727 individuals. The diversity index values indicate moderate species richness, highlighting the park’s ecological significance. Compared to previous studies, which primarily focused on megafauna, this research emphasizes avian biodiversity as a novel approach to contextual learning. The findings demonstrate that incorporating local avifauna into the curriculum enhances students' understanding of ecosystem dynamics, biodiversity conservation, and species adaptation. This study provides practical implications for biology education by promoting field-based learning, fostering conservation awareness, and encouraging schools to integrate local biodiversity into teaching materials. Strengthening collaboration between educators, conservationists, and local communities is crucial for maximizing the educational benefits of regional biodiversity.